NILAI BUDAYA, PENGASUHAN PENERIMAAN-PENOLAKAN, DAN PERKEMBANGAN SOSIAL ANAK USIA 3-5 TAHUN PADA KELUARGA KAMPUNG ADAT URUG, BOGOR - Permatasari, Cefti Lia; Hastuti, Dwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2013)
The aim of the research was to analyze the cultural values, parental acceptance-rejection, and social development of 3-5 years old children at Kampung Adat Urug families, Bogor. This research involved 60 samples that were selected by proportional random sampling. Data collected by interview and observation. Social development was measured by Vineland Social Maturity Scale (VSMS). Data was analyzed by descriptive and Spearman correlation test. The results showed that mostly parents in this research applied higher parental acceptance which is indicated by the affection/ warmth from the parents. Girls more accepted and parents more likely to be warm than to boys. Parental acceptance-rejection correlated significantly with sex and social activity of mother. The results also showed that more than a half children had social development in moderate categorize. Girls had better social development than boys. Social development correlated significantly with education and social activity of mother. Social development didn’t correlate significantly with parental accepatance-rejection.